The Analysis of Moral Values in The Black Saxons by Lydia Maria Child - Maharini, May Triranto (CV. Pena Persada, 2018)
This research analyzed the moral values in The Black Saxons, a nineteenth century short story by Lydia Maria Child. It aimed to show the relativity of moral values to slavery portrayed in the story. Jacques Thiroux‘s five basic moral principles, which are the values of life, goodness or rightness, individual freedom, justice or fairness, and honesty were used for this analysis. The writer hopes the study would be beneficial for English literature students in college.